Las editoriales independientes en el punto de mira literario: balance y perspectivas teóricas - Ana Gallego Cuiñas (Caravelle)
This paper aims to define the material and cultural practices of the independent Latin American publishers of the 21st century, a phenomenon that has recently captured the Academy’s attention, from the categories of literary theory and criticism, in dialogue with the sociology of culture. Thus, we will focus on the Argentinian case to delimit a series of concepts that explain the literary, political and social values of independent publishers: anachronism, aura, community, bibliodiversity, decolonial materialism, gatekeeper.